Repair of Septal Perforations - Kimura, Kyle S.; Ortiz, Alexandra S.; Stephan, Scott J. (Facial Plastic Surgery, 2022)
Nasal septal perforations have varied etiologies, clinical presentations, and methods of management. Some patients may be asymptomatic, while others may complain of nasal obstruction, crusting, epistaxis, and whistling. Management of nasal septal perforations is guided by the patient's symptoms and characteristics of the perforation. Some lesions can be managed conservatively or with minimally invasive procedures, while others require surgery. Surgical repair of perforations can be challenging and many techniques have been described without a standardized method of management. This article aims to provide a comprehensive review of options for repair of nasal septal perforations.
Keywords: nasal septal perforation; nasal septum; pedicled flap; mucosal flap; interposition graft; temporalis fascia